Computer Simulation on Prediction of Possible Locations of Rupture in an Abdominal Aortic Aneurysm (AAA) - Maranon, Dioscoro P.; Paran, Alexander P.; Publico, Andre S.; Quintos III, Ricardo T. (Silliman Journal, 2023)
From a biomechanical point of view the possible locations of rupture in an abdominal aortic aneurysm (AAA) could be those points that are subjected to high wall stresses. Where and when rupture will occur in an AAA cannot be predicted. If these locations of rupture can be identified, proper surgical intervention is possible. The present study makes use of images from Com-puter Tomography (CT) scans of a patient which when converted to solid models using the 3-0 solid modeling software can then be analyzed with the Finite Element Analysis (FEA).